Pengaruh Motivasi dan Disiplin Kerja Terhadap Peningkatan Produktivitas Kerja di Pondok Pesantren - Zayudi Anwar; Kaharuddin, M. Robby; fitria; Mega Satria (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
This research aims to determine the influence of work motivation and discipline on increasing work productivity at the Al Furqon Modern Islamic Boarding School. This type of research is quantitative using multiple linear regression analysis methods using SPSS 16.0 software. Based on the results of the partial test, motivation (X1) with a t value of 1.304 is smaller than t table or the t test significance value of 0.195 is greater than 0.05 (a = 5%), then it is stated that partial motivation (X1) has no significant effect on increase in work productivity (Y). Work discipline (X2) with a t value of 1.040 greater than t table 1.657 or a significance value of 001 smaller than 0.05 (a = 5%), then it is stated that discipline (X2) has no significant effect on increasing work productivity (Y ). Based on the results of the simultaneous test or F test, it shows that work motivation and discipline with a fcount value of 1.330 is greater than ftable 3.07 (1.330 > 3.07) and a significance value of 0.268 is greater than 0.05, so motivation is stated together. (X1) and discipline (X2) have a positive and significant effect on increasing work productivity (Y).